Assistive Technology and Internet of Things for people with ADHD - Moraiti, Ioanna; Fotoglou, Anestis; Dona, Katerina; Katsimperi, Alexandra; Tsionakas, Konstantinos; Karampatzaki, Zoi; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
This article focuses on how people with disabilities can benefit from new technologies and in particular assistive technology and Internet of Things Applications. Assistive Technology is now an integral part of modern education and even more in the field of special education, as it can prove to be a powerful tool to support educational integration. Through smart devices and artificial intelligence, an attempt is made to recognize emotions and the level of arousal, through sensors, restoring it to a normal basis, and giving continuous emotional feedback. This paper refers to parents, caregivers, and people with ADHD and it gives solutions that improve their daily lives with the help of applications created for smart devices.